2015
DOI: 10.4103/2454-6798.165089
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and incorporation of tumor volume data in staging and prognostication of head and neck squamous cell carcinoma treated with definitive radiotherapy: A systematic review

Abstract: Head and neck squamous cell cancers (HNSCC) are a group of heterogeneous tumors, evident by their diverse behavior and natural history. The largest diameter of tumor measured for T classification may not necessarily reflect the true tumor dimension. There is a need to take into account certain other feature(s) of these tumors other than the maximum single dimension which can reflect the true tumor burden more accurately. Tumor volume has been shown to be a useful and accurate tool burden because it is a measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
(105 reference statements)
0
2
0
Order By: Relevance
“…This is a simple and easy way to obtain information, which has not been properly evaluated in operated tumors. Previous studies have suggested that tumor volume should be incorporated into staging systems …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a simple and easy way to obtain information, which has not been properly evaluated in operated tumors. Previous studies have suggested that tumor volume should be incorporated into staging systems …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that tumor volume should be incorporated into staging systems. [64][65][66][67] The value used as a cutoff for volume measurement stratification was 33.6 cc. Hypothetically, a lesion measuring 3.9 cm 3 3.5 cm 3 2.5 cm would fulfill this criterion.…”
Section: Discussionmentioning
confidence: 99%